Light-activated phenalen-1-one bactericides: efficacy, toxicity and mechanism compared with benzalkonium chloride. (November 2017) - Muehler, Denise; Sommer, Kerstin; Wennige, Sara; Hiller, Karl-Anton; Cieplik, Fabian; Maisch, Tim; Späth, Andreas
Aim: Five photoactive compounds with variable elongated alkyl-substituents in a phenalen-1-one structure were examined in view of structural similarity to the antimicrobial agent benzalkonium chloride (BAC).Methods: All phenalen-1-ones and BAC were evaluated for their antimicrobial properties against Staphylococcus aureus, methicillin-resistant S. aureus, Escherichia coli, Pseudomonas aeruginosa and for their eukaryotic toxicity against normal human epidermal keratinocyte (NHEK) cells to narrow down the BAC-like effect and the photodynamic effect depending on the chemical structure. All compounds were investigated for effective concentration ranges, where a bacterial reduction of 5 log10 is achieved, while an NHEK survival of 80% is ensured.Results: Effective concentration ranges were found for four out of five photoactive compounds, but not for BAC and the compound with BAC-like alkyl chain length.Conclusion: Chain length size and polar area of the respective head-groups of phenalen-1-one compounds or BAC showed an influence on the incorporation inside lipid membranes and thus, head-groups may have an impact on the toxicity of antimicrobials.